Réponses

Meilleure réponse !
  • Utilisateur Brainly
2014-03-09T19:13:02+01:00
Développement et réduction:

A= 11 + 2 (x - 6)
A= 11 + 2x -12
A= 2x -1

B= -3 (2y - 4) -2y
B= -6y +12 -2y
B= -8y + 12

C= 7 - 4 (8 - 2a)
C= 7 -32 + 8a
C= 8a -25

Voilà ! J'espère t'avoir aidé ! :)
2014-03-09T19:14:55+01:00
Salut :)

A = 11 + 2(x - 6)
A = 11 + 2 x (x) + 2 x (-6)
A = 11 +2x - 12
A = 2x - 1

B = -3(2y - 4) - 2y
B = -3 x 2y - 3 x (-4) - 2y
B = -6y + 12 - 2y
B = -8y + 12

C = 7 - 4(8 - 2a)
C = 7 - 4 x 8 - 4 x (-2a)
C = 7 - 32 + 8a
C = 8a - 25

J'espère t'avoir aidé(e)! :)